CODESRIA Bulletin, No. 4, 2020 - Journal System (CODESRIA Bulletin, 2020)
In this issue Editorial, Godwin R. Murunga & Ibrahim O. Ogachi ———— 1 1. The Randomista Rampage in Development Economics: A View from the Trenches, David Ndii ——3 2. Evidence as Cliché: Using Trials to Tamper with Governance, Seye Abimbola———– 9 3. The Nobel Prizes, Racism, and the Economy of Prestige, Wandia Njoya ————- 17 4. Economics Experiments in Africa: How Many and by Whom? Amma Panin ———— 23 5. Structural Change, Inequality, and Inclusive Development: Case of Sub-Saharan Africa, Jimi Adesina ——– 29 6. ‘Mandela-wash’: How Invoking Mandela’s Name Cannot Obscure Past Injustice, Robin Cohen ——– 37